Formation of educational motivation of younger schoolchildren in conditions of different technical equipment of the educational process - Viktoriia V. Usoltseva; Natalia G. Pidtsan; Alexandra V. Dorokhova (Развитие образования, 2023)
The article presents an analysis of the formation of educational motivation of younger schoolchildren in conditions of different technical equipment of the educational process. The relevance of the research is determined by the fact that in the modern world there is an active development of new technologies. Competent use of technical equipment in the educational process can only develop students' interest in obtaining knowledge, thereby increasing their level of educational motivation. The purpose of the study is to study the formation of educational motivation of younger schoolchildren in conditions of different technical equipment of the educational process. The authors hypothesized that younger schoolchildren studying in conditions of good technical equipment of the educational process have a higher level of motivation for educational activities. The sample set of the study was made up of students of the 2nd and 4th grades of budgetary educational institutions “secondary school №. 124”, “secondary school № 30”. The stages and the complex of psychological techniques are described. Features of conducting and results of the study of educational motivation of students of schools with different technical equipment. The study was conducted by testing the typology of teaching motives, assessing school motivation and its level in elementary school students. In conclusion, the article presents conclusions about the presence of differences in the educational motivation of students in different conditions of technical equipment. It was found that students of the 2nd grades in the conditions of modern equipment of the educational process are more motivated to study.